Recent Referees (Journal of Political Economy, 2020)
Previous articleNext article FreeRecent RefereesFull TextPDF Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Eliot AbramsSumit AgarwalDavid AlbouyDiane AlexanderS. Nageeb AliTreb AllenPeter ArcidiaconoAshish AroraJohn AskerMiguel BallesterBjoern BartlingDaniel BenjaminMarianne BertrandChristopher BlattmanAlessandro BonattiStephane BonhommeLeah BoustanChristine BraunNick BuchholzKonrad BurchardiAntonio CabralesSydnee CaldwellAlexander CappelenPedro CarneiroJuan CarrilloLaurent CavenaileThomas ChaneyGary CharnessJay ChoiGian ClementiJohn CochraneAlain CohnJuan Carlos ConesaKimberly CornaggiaLucia CornoMarco CosconatiVincent CrawfordMichael CunaGordon DahlAluma DemboDavid DemingEllora DerenoncourtManasi DeshpandeMichael DicksteinWill DobbieMatthias DoepkeGregory DowJoseph DoyleWioletta DziudaItzik FadlonPablo FajgelbaumJames FenskeJames FeyrerRaymond FismanEric FrenchJoshua GansJorge Luis GarcíaAlexander GelberChristian GillitzerGreer GosnellDavid GreenJohn GrigsbyWilliam HanlonAnne HannuschBruce HansenBenjamin HebertOri HeffetzTibor HeumannMartin HolmRichard HornbeckErik HornungHanan JacobyTomas JagelkaPankaj JainBenjamin JohannsenCharles JonesSteven KaplanLouis KaplowMaxwell KelloggWilliam KerrBen KeysIgor KopylovTheresa KuchlerMichael KuhnLuc LaevenJoanna LaheyDarius LakdawallaTimothy LaytonJustin LeungTim LeunigRoss LevineJean-Paul L’HuillierAttila LindnerMatthew LindquistAriel ListoMeng LiuKatrine LokenErzo LuttmerSergey LychaginEsfandiar MaasoumiMario MacisBartosz MackowiakGlenn MagermanAsier MariscalAlisdair McKayDavid McLeanDaniel McMillenHalvor MehlumJoel MokyrDavid MolitorJohn MorrowJack MountjoyKaivan MunshiTom NicholasJuan NicoliniEric NielsenThomas NoeKevin O’RourkeHarry PeiJesse PerlaFelix PretisLouis PuttermanThomas QuanPablo QuerubinDaniel RappoportM. RehaviA. ReynosoRichard RobbArthur RobsonPauline RossiMaya Rossin-SlaterAriel RubinsteinAldo RustichiniNicholas RyanJohn SabelhausDaniel SacksMolly SchnellAndrew SchotterCarsten SchroederHannes SchwandtMariel SchwartzJesse ShapiroJoseph ShapiroAndrew ShephardRon SiegelOlmo SilvaLuis SimonKerry SmithLones SmithErik SnowbergGary SolonOlav SorensonFrancesco SquintaniJakub SteinerJoel StiebaleJan StoopJohannes StroebelMelissa ThomassonHaruka UchidaCan UrgunWinnie van DijkStijn Van NieuwerburghJohn Van ReenenAndrea WilsonDaniel WilsonLudger WoessmannEdward WolffJiro YoshidaPaolo ZacchiaBasit ZafarAndy ZapechelnyukLu ZhangOwen Zidar Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 128, Number 3March 2020 Article DOIhttps://doi.org/10.1086/708760 Views: 129 © 2020 by The University of Chicago. All rights reserved. Crossref reports no articles citing this article.